A case of visceral leishmaniasis and pulmonary tuberculosis in a post-partum woman. (April 2015) - Colomba, Claudia; Adamoli, Lucia; Trizzino, Marcello; Siracusa, Lucia; Bonura, Silvia; Tolomeo, Manlio; Cajozzo, Massimo; Giammanco, Giovanni Maurizio
Highlights: Pregnancy is accompanied by changes in immune response. Co-infection of visceral leishmaniasis and tuberculosis is an important public problem. Evaluation of the diagnosis of leishmaniasis in pregnant women with fever and haematological abnormalities would be necessary in an endemic area. Abstract: Visceral leishmaniasis due to Leishmania infantum is a vector-borne zoonotic disease transmitted by sand fly bites endemic in rural or periurban areas of the Mediterranean basin. Pregnancy is accompanied by changes in immune response, mainly a decrease in cellular immunity and a proportional increase in humoral immunity. These physiological events result in increased risk of infection by pathogens whose immunity is based on a T-helper 1 predominant response. We describe a case of visceral leishmaniasis and pulmonary tuberculosis diagnosed in a post-partum woman four days after delivery. The diagnosis of leishmaniasis should be considered in pregnant women with fever and haematologic abnormalities in endemic regions or if a history of exposure in endemic areas is reported.